2022
DOI: 10.1186/s12889-022-13949-5
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in prevalence of hypertension among Indians across various age-groups: a report from multiple nationally representative samples

Abstract: Background Prevalence of hypertension increases with age, but there is a general perception in India that women are less affected at every stage of life, although empiric evidence hardly exists regarding gender difference in hypertension in Indians of different ages. Therefore, we aimed to examine the gender difference in hypertension among Indians across various age-groups; and the contribution of variation in body mass index (BMI) to this difference. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…The results showed geographical differences in the prevalence of hypertension among Ganzhou residents, which could be due to the variation in the geographical environment and economic development of the districts [ 6 , 10 ]. Both univariate and multivariate logistic regression indicated that age and sex correlated with hypertension, which is consistent with previous findings [ 17 ]. With aging and physiological deterioration, for example, early vascular aging, the occurrence of various diseases (such as hypertension) inevitably increases [ 2 , 18 ].…”
Section: Discussionsupporting
confidence: 91%
“…The results showed geographical differences in the prevalence of hypertension among Ganzhou residents, which could be due to the variation in the geographical environment and economic development of the districts [ 6 , 10 ]. Both univariate and multivariate logistic regression indicated that age and sex correlated with hypertension, which is consistent with previous findings [ 17 ]. With aging and physiological deterioration, for example, early vascular aging, the occurrence of various diseases (such as hypertension) inevitably increases [ 2 , 18 ].…”
Section: Discussionsupporting
confidence: 91%
“…Estimated age range for male population regarding incidence of hypertension only and hypertension with comorbidity was between 25-105 years and 23-100 years respectively. These descriptions show that incidence of hypertension and hypertension with comorbidity occur in female populations earlier than males and this is supported by research studies [31][32] that examined gender differences in the prevalence of hypertension across various age groups and potential association of gender-specific factors for hypertension. A comprehensive cardio-metabolic risk assessment of gender found females to be at high risk than males and among gender specific factors, age (younger age) at childbirth was found to be among the high risk factors for women.…”
Section: Discussionmentioning
confidence: 73%
“…Globally, women have a slightly greater prevalence of hypertension as compared to males, but in our study, women had a slightly higher prevalence. [ 10 ] Most of the patients belonged to the rural areas. In literacy, only 28.7% received secondary education followed by greater number of the patients being illiterate (27.3%).…”
Section: Discussionmentioning
confidence: 99%